2019
DOI: 10.1097/md.0000000000013942
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of treatment methods for pediatric Monteggia fracture

Abstract: Various methods are applied in the treatment of fresh and neglected Monteggia fractures. The purpose of this retrospective study was to evaluate the efficacy of various treatment methods, and assess the complexity associated with missed radial head dislocation.All fracture patients were reviewed between Jan 2012 and Dec 2016. A detailed comparison was made of the treatment methods between fresh Monteggia fractures and neglected Monteggia fractures with missed diagnosis of dislocation.A preliminary analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 17 publications
3
35
0
Order By: Relevance
“…He et al observed similar results in acute Monteggia fracture dislocations which were managed surgically. 6 Korani in his study achieved good results in 62.5% cases which is comparable to our study. 8…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…He et al observed similar results in acute Monteggia fracture dislocations which were managed surgically. 6 Korani in his study achieved good results in 62.5% cases which is comparable to our study. 8…”
Section: Discussionsupporting
confidence: 89%
“…He et al also noted the same trend in their study. 6 Bado classification was used to describe Monteggia fracture dislocation. Bado classification based on the direction of the radial head in fracture; in type I the head is anterior, type II is posterior, type III is lateral and in type IV there is a dislocation of the radial head associated with a fracture of both the radius and ulna.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 13 ] This approach is effective if the time from injury is less than 4 to 6 months, and the shape of the ulna is not compromised. [ 14 , 15 ] Besides, reduction without exposing the RCJ has also been reported using ulnar lengthening angulation osteotomy. [ 16 , 17 ] Moreover, certain authors recommend UO combined with open reduction of RHD.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, intramedullary nailing fixation is the main method of fracture stabilization in acute, stable and unstable Monteggia injuries, while plate fixations are widely used in patients with neglected Monteggia fractures[ 15 ]. Many authors use a cut-off of fourweeks before considering a Monteggia fracture to be “neglected”.…”
Section: Discussionmentioning
confidence: 99%